PENERAPAN METODE SMART DALAM PEMILIHAN PERPUSTAKAAN TINGKAT SMP TERBAIK DI KOTA MAKASSAR - Ichsan Jaylani; Muhammad Fitrah Rivan; Andi Harmin; Asri Yadi (P3M STMIK Profesional Makassar, 2025)
The library plays a crucial role in supporting education and literacy. However, determining the best library in Makassar, particularly at the junior high school level, remains challenging due to various qualitative factors. This research applies the Simple Multi Attribute Rating Technique (SMART) method to evaluate and rank libraries objectively based on seven criteria: book collection, facilities, service, accessibility, innovation and technology, literacy activities, and cleanliness and safety. Data was collected through observations, questionnaires, and interviews across selected libraries in Makassar. The system developed provides a decision support tool that calculates weighted scores and recommends the best-performing library. Results show that SMART effectively delivers transparent and structured decision-making to support library quality assessment and policy recommendations.